2005
DOI: 10.1136/oem.2005.021550
|View full text |Cite
|
Sign up to set email alerts
|

Risk of lymphatic or haematopoietic cancer mortality with occupational exposure to animals or the public

Abstract: Background: Occupational exposure to animals or the public could result in exposure to infectious agents, which may play a role in the aetiology of lymphohaematopoietic (LH) cancers. Aims: To conduct a population based, case-control study of death certificate data from 1984 to 1998 in 24 US states in order to evaluate the risk of mortality from LH neoplasms associated with occupational exposure to animals or the public. Methods: Cases were selected as those with an underlying cause of death of non-Hodgkin's ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
1
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 74 publications
2
48
1
2
Order By: Relevance
“…Four studies reported an association with NHL; seven reported no association; and none reported an inverse association. Results for employment in farming of specific crops and livestock breeding were analyzed separately: four risk estimates for crop farming (5,(26)(27)(28) and six (4,5,23,(26)(27)(28) for animal breeding (Supplementary Table S3). Only one of the studies on crop farming reported an association with NHL, whereas four of six studies on animal breeding reported an association with NHL.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four studies reported an association with NHL; seven reported no association; and none reported an inverse association. Results for employment in farming of specific crops and livestock breeding were analyzed separately: four risk estimates for crop farming (5,(26)(27)(28) and six (4,5,23,(26)(27)(28) for animal breeding (Supplementary Table S3). Only one of the studies on crop farming reported an association with NHL, whereas four of six studies on animal breeding reported an association with NHL.…”
Section: Methodsmentioning
confidence: 99%
“…Five studies (5,6,17,19,28) of school teachers published after the meta-analysis were identified (Supplementary Table S4), of which three reported an association with NHL. These five new studies were analyzed together with the 13 studies included in the meta-analysis (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…Occupational exposure to beef cattle was associated significantly with NHL (OR 5 1.8, 95% CI: 1.1-2.9), but no association was observed for dairy cattle (OR 5 0.9, 95% CI: 0.5-1.6). 633 Svec et al 264 reported a significant positive association between NHL and animal exposure among farming occupations (OR 5 1.25, 95% CI: 1.19-1.31) in a case-control study of death certificate data in 24 US states.…”
Section: Interactions With Environment and Lifestyle Factorsmentioning
confidence: 99%
“…A significant positive association was found for farming occupations with animal exposure (OR 5 1.24, 95% CI: 1.17-1.32) in a case-control study of death certificate data from 24 US states. 85 Semenciw et al 71 evaluated farming practices in the prairie provinces of Canada in a retrospective cohort study and found no evidence of an exposure-response relationship based on the size of poultry or cattle farms; the relative risk estimates for each quartile were 1.0. Similar findings were observed in 2 recently published Canadian population-based case-control studies.…”
Section: Agriculture and Farmingmentioning
confidence: 99%